Braiding sweetgrass - Kimmerer, Robin Wall (2013)
"As a leading researcher in the field of biology, Robin Wall Kimmerer understands the delicate state of our world. But as an active member of the Potawatomi nation, she senses and relates to the world through a way of knowing far older than any science. In Braiding Sweetgrass, she intertwines these two modes of awareness--the analytic and the emotional, the scientific and the cultural--to ultimately reveal a path toward healing the rift that grows between people and nature. The woven essays that construct this book bring people back into conversation with all that is green and growing; a universe that never stopped speaking to us, even when we forgot how to listen"--
Planting Sweetgrass. Skywoman Falling ; The Council of Pecans ; The Gift of Strawberries ; An Offering ; Asters and Goldenrod ; Learning the Grammar of Animacy -- Tending Sweetgrass. Maple Sugar Moon ; Witch Hazel ; A Mother's Work ; The Consolation of Water Lilies ; Allegiance to Gratitude -- Picking Sweetgrass. Epiphany in the Beans ; The Three Sisters ; Wisgaak Gokpenagen: a Black Ash basket ; Mishkos Kenomagwen: The Teachings of Grass ; Maple Nation: A Citizenship Guide ; The Honorable Harvest -- Braiding Sweetgrass. In the Footsteps of Nanabozho: Becoming Indigenous to Place ; The Sound of Silverbells ; Sitting in a Circle ; Burning Cascade Head ; Putting Down Roots ; Umbilicaria: The belly Button of the World ; Old-Growth Children ; Witness to the Rain -- Burning Sweetgrass. Windigo Footprints ; The Sacred and the Superfund ; People of Corn, People of Light ; Collateral adamage ; Shkitagen: People of the Seventh Fire ; Defeating Windigo -- Epilogue: Returning the Gift
Includes bibliographical references (pages 387-388)
Keywords: Indian philosophy; Ethnoecology; Philosophy of nature; Human ecology -- Philosophy; Nature -- Effect of human beings on; Human-plant relationships; Botany -- Philosophy; Potawatomi Indians -- Biography; Potawatomi Indians -- Social life and customs